Halal bi Halal Sebagai Momentum Rekonsiliasi dan Penguatan Silaturrahmi - Khusnul Mufida (La-Tahzan: Jurnal Pendidikan Islam, 2024)
Halal bi halal is a typical tradition of Indonesian society which is carried out every Eid al-Fitr, namely in the month of Shawwal. This tradition is also an important moment for reconciliation and strengthening the bonds of friendship amidst the diversity of society. This tradition teaches values such as empathy, understanding, and humility, creating a harmonious atmosphere and strengthening social relations. This article is written to find out how important halal bi halal is as a form of reconciliation and strengthening of friendship amidst the diversity of Indonesian society. This paper is a literature study that makes the halal bi halal tradition have an important position in society. In Indonesia, which is rich in diversity, halal bi halal is an effective tool to unite the community and repair damaged relationships. So this tradition needs to be maintained and preserved to build a more peaceful and harmonious society.